The Prevalence of Premature Loss of Primary Molars Among Children Who Attended College of Dentistry/Hillah City, Iraq - Sarah Y. Al Khafaji; Zahraa Mohamed Hussain Wais; Omaima Lateef Salman (Medical Journal of Babylon)
Background: Early tooth loss can compromise the integrity of the arch length required for subsequent permanent teeth, causing crowding, rotation, and impaction of the permanent teeth. Objective: The objective of this study is to assess the frequency of early primary molar loss at the dentistry college in Hillah, Iraq. Materials and Methods: An experienced examiner performed each clinical examination while using the proper illumination. For the study, a total of 206 children (84 boys and 122 girls) between the ages of 5 and 10 were chosen. Age and tooth loss were among the information gathered. The acquired data were then subjected to statistical analysis. All statistical calculations are made using the SPSS version 26 software. The Pearson chi-squared test and Cramer V test are used to assess categorical variables, which are provided as absolute numbers and percentages. P values lower than 0.05 were regarded as significant. Result: The study found that in the sample, 69.83% had early loss of primary teeth with girls having a higher incidence of primary tooth loss than boys (59.2%). Both first and second molars are affected with premature loss equally. Premature tooth loss was significant in the mandibular left side (36.9%). Conclusion: Early primary tooth loss was shown to be more common significantly in girls when compared to boys. The left mandibular tooth was most commonly affected, then right side followed by maxillary right and left side sequentially. First and second molars are equally affected with premature loss.